2022
DOI: 10.1111/jgh.15999
|View full text |Cite
|
Sign up to set email alerts
|

Role of m6A RNA methylation in the development of hepatitis B virus‐associated hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common liver malignancy that can be developed from hepatitis B and cirrhosis. Many pathophysiological alterations, including hepatitis B virus (HBV) DNA integration, oxidative stress, cytokine release, telomerase homeostasis, mitochondrial damage, epigenetic modification, and tumor microenvironment, are involved in the biological process from hepatitis B to cirrhosis and HCC. N6-methyladenosine (m6A), as an epitranscriptomic modification of RNAs, can regulate the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 151 publications
0
4
0
Order By: Relevance
“…Based on these studies, m6A expression levels can cause bilateral effects. However, m6A is known to play a regulatory role in many biological activities such as immune response, tumourigenesis, and viral replication [33][34][35]. When we compared the stem-loop structure of DCH and HBV epsilon by secondary structure analysis, we found that they have almost the same conformation on the X protein, although the nucleotide spacing is different.…”
Section: Full Textmentioning
confidence: 93%
See 1 more Smart Citation
“…Based on these studies, m6A expression levels can cause bilateral effects. However, m6A is known to play a regulatory role in many biological activities such as immune response, tumourigenesis, and viral replication [33][34][35]. When we compared the stem-loop structure of DCH and HBV epsilon by secondary structure analysis, we found that they have almost the same conformation on the X protein, although the nucleotide spacing is different.…”
Section: Full Textmentioning
confidence: 93%
“…Recent literature suggests that N6-methyladenosine (m6A) modi cation may play an important role in the regulation of the hepadnaviral life cycle [33][34][35]. As the most abundant epitranscriptomic internal modi cation factor, m6A can be expressed by cellular or viral RNAs.…”
Section: Full Textmentioning
confidence: 99%
“…Chronic HBV infection is a major cause of liver fibrosis and progression to hepatocellular carcinoma (49). Given the known role of both m 6 A and HBV in HCC development and progression, and the known role of m 6 A on HBV replication cycle and protein translation, we were interested in whether disruption of m 6 A modification in Mettl14 [fl/fl] /Alb-Cre mice would impact outcomes of HBV exposure (15,(50)(51)(52).…”
Section: Hbv Genome Induced Hepatic Inflammation Is Worsened In Mettl...mentioning
confidence: 99%
“…Increasing evidence indicates that RNA methylation plays a crucial role in tumorigenesis, and dysregulation of RNA methylation has been observed in various cancers including HCC [ 60 64 ]. Elucidating the multifaceted mechanisms of RNA modifications in the genetic pathogenesis of HCC is increasingly getting considered as a valuable direction for the clinical management of HCC [ 40 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%